2021
DOI: 10.1108/jima-12-2019-0267
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of customer financial condition in the acceptance of Islamic microfinance in a frontier market

Abstract: Purpose The study aims to identify a gap within the extant literature on the inadequacy of earlier extension of the theory of reasoned action (TRA) and theory of planned behavior (TPB) to accommodate the peculiarity of Muslims majority countries that experiencing poverty growth in modeling the factors influencing the acceptability of Islamic financial products and services. To address this gap, this study expands the aforementioned theories through the integration of customer financial condition through the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“… [ 80 , 88 ] Examine the impact of client financial circumstances on the adoption of Islamic microfinance, along with other Islamic financial products and services, and assess the potential for market expansion in the agricultural industry, aiming to generate a positive social impact through poverty reduction and job creation. [ 101 ] Explore additional ratios that can shed light on the profitability factors of various firms within the finance sector. [ 87 ] Exploring the inclusion of cultural variables and examining the impact of digitalization would be valuable avenues for further exploration in the field.…”
Section: Future Research Directionmentioning
confidence: 99%
“… [ 80 , 88 ] Examine the impact of client financial circumstances on the adoption of Islamic microfinance, along with other Islamic financial products and services, and assess the potential for market expansion in the agricultural industry, aiming to generate a positive social impact through poverty reduction and job creation. [ 101 ] Explore additional ratios that can shed light on the profitability factors of various firms within the finance sector. [ 87 ] Exploring the inclusion of cultural variables and examining the impact of digitalization would be valuable avenues for further exploration in the field.…”
Section: Future Research Directionmentioning
confidence: 99%
“…(Purwanto, Abdullah, Ghofur, Abdullah, & Elizabeth, 2022) Adoption of Islamic microfinance in Indonesia an empirical investigation: an extension of the theory of planned behaviour 9. (Umar, Mas'ud, & Matazu, 2022) Direct and indirect effects of customer financial condition in the Acceptance of Islamic Microfinance in a frontier market 10. (Utomo, Sekaryuni, Widarjono, Tohirin, & Sudarsono, 2020) Promoting Islamic financial ecosystem to improve halal industry performance in Indonesia: a demand and supply analysis Several conclusions can be drawn from previous research regarding the determinants of intention to use Islamic financing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The amount of this higher loan ranges from BDT 30,000 (about USD 375) to BDT 200,000 (about USD 2500), and the users can apply for it once they have successfully repaid the lower loan (MFIs). Some of the ideas it promotes are: doing good things, obeying the law and not doing anything illegal, becoming self-reliant for success, raising wellness awareness, and getting an education [9,30]. Users of group loans are required to pay their complete financial responsibilities (principal amount with income) in 44 equal instalments every week, regardless of the loan they have taken out [30].…”
Section: The Model For Rural Development Scheme (Rds)mentioning
confidence: 99%
“…Several studies that were done not too long ago showed that MFIs' financial performance was going down. Because of this, it is essential to study how well MFIs work [9]. The Microfinance Banking (MFB) and NGO-MFIs' operational and financing techniques are precisely replicated by the RDS, but the sorts of operations and items offered by IsMFIs are distinct from those of MFB and NGO-MFIs.…”
Section: Introductionmentioning
confidence: 99%